Results from the experimental evaluation of CeBr3 scintillators for 4He prompt gamma spectroscopy - Dal Bello, Riccardo; Magalhães Martins, Paulo; Graça, João; Hermann, German; Kihm, Thomas; Seco, Joao (Medical physics, 2019)
Purpose The presence of range uncertainties hinders the exploitation of the full potential of charged particle therapy. Several range verification techniques have been proposed to mitigate this limitation. Prompt gamma spectroscopy (PGS) is among the most promising solutions for online and in vivo range verification. In this work, we present the experimental results of the detection of prompt gamma radiation, induced by He beams at the Heidelberg Ion-Beam Therapy Center (HIT). The results were obtained, using a spectroscopic unit of which the design has been optimized using Monte Carlo simulations. Methods The spectroscopic unit is composed by a primary cerium bromide (CeBr) crystal surrounded by a secondary bismuth germanate (BGO) crystal for anticoincidence detection (AC). The digitalization of the signals is performed with an advanced FADC/FPGA system. The He beams at clinical energies and intensities are delivered to multiple targets in the experimental cave at the HIT. We analyze the production of prompt gamma on oxygen and carbon targets, as well as high Z materials such as titanium and aluminum. The quantitative analysis includes a systematic comparison of the signal-to-noise ratio (SNR) improvement for the spectral lines when introducing the AC detection. Moreover, the SNR improvement could provide a reduction of the number of events required to draw robust conclusions. We perform a statistic analysis to determine the magnitude of such an effect. Results We present the energy spectra detected by the primary CeBr and the secondary BGO. The combination of these two detectors leads to an average increase of the signal-to-noise ratio by a factor 2.1, which confirms the Monte Carlo predictions. The spectroscopic unit is capable of detecting efficiently the discrete gamma emission over the full energy spectrum. We identify and analyze 19 independent spectral lines in an energy range spacing from MeV to MeV. Moreover, when introducing the AC detection, the number of events required to determine robustly the intensity of the discrete lines decreases. Finally, the analysis of the low-energy reaction lines determines whether a thin metal insert is introduced in the beam direction. Conclusions This work provides the experimental characterization of the spectroscopy unit in development for range verification through PGS at the HIT. Excellent performances have been demonstrated over the full prompt gamma energy spectrum with He beams at clinical energies and intensities.
Im Titel ist die Zahl "3" tiefgestellt, die Zahl "4" hochgestellt
Gesehen am 19.01.2021